EXPERIMENTAL INVESTIGATION OF D-GLUCOSAMINE INFLUENCE ON INTRAUTERINE DEVELOPMENT OF FETAL RATS - Shevchenko, O.I.; Storchak, A.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
It was performed an assessment of possible teratogenic and embryotoxic effects on female rats. It was calculated the quantity of luteal glands in rats ovaries, quantity of alive and newborn rats, also was evaluated the lethal effects before and after implantation, macroscopic assessment to determine visible malformation, investigation of internal organs and bony skeleton. The obtained data demonstrates the absence of embryolethal effect of D-glucosamine dose 90mg/kg. We had proved the absence of visible malformations in 20 days fetuses included skeleton malformations. So it was concluded that D-glucosamine had no teratogenic effects. These results was the only first step to D-glucosamine application in perinatology.